2018
DOI: 10.1002/adhm.201701290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graphene on the Efficacy of Neuron Culture Substrates

Abstract: How graphene influences the behavior of living cells or tissues remains a critical issue for its application in biomedical studies, despite the general acceptance that graphene is biocompatible. While direct contact between cells and graphene is not a requirement for all biomedical applications, it is often mandatory for biosensing. Therefore, it is important to clarify whether graphene impedes the ability of cells to interact with biological elements in their environment. Here, a systematic study is reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Although the direct contact between graphene and RGCs induced higher cation activity than those pristine substrate matrix, decreased inward and outward currents from patch‐clamp recording results indicated a reduction in the number of voltage‐gated Na + /K + ion channels. These results revealed that graphene would not obviously alter overall electrophysiology properties of neurons, despite the reported change in phenotype and cellular behaviors. Pampaloni et al recently proposed that neuronal excitability was modified by single layer CVD grown graphene on electrically insulating substrates, which may be one reasonable explanation to these interesting cellular behaviors .…”
Section: Graphene‐based Scaffolds For Neurogenesis and Myogenesismentioning
confidence: 82%
See 1 more Smart Citation
“…Although the direct contact between graphene and RGCs induced higher cation activity than those pristine substrate matrix, decreased inward and outward currents from patch‐clamp recording results indicated a reduction in the number of voltage‐gated Na + /K + ion channels. These results revealed that graphene would not obviously alter overall electrophysiology properties of neurons, despite the reported change in phenotype and cellular behaviors. Pampaloni et al recently proposed that neuronal excitability was modified by single layer CVD grown graphene on electrically insulating substrates, which may be one reasonable explanation to these interesting cellular behaviors .…”
Section: Graphene‐based Scaffolds For Neurogenesis and Myogenesismentioning
confidence: 82%
“…could affect cell–substrate adhesion, cell proliferation, and neuronal differentiation of stem cells . In another work, Fischer et al investigated whether the addition of a graphene monolayer on top of laminin/Poly‐ d ‐lysine (PDL) coated glass substrate could influence the RGCs–substrate interactions, which reveals that graphene did not significantly influence the cell viability and vitality . Although the direct contact between graphene and RGCs induced higher cation activity than those pristine substrate matrix, decreased inward and outward currents from patch‐clamp recording results indicated a reduction in the number of voltage‐gated Na + /K + ion channels.…”
Section: Graphene‐based Scaffolds For Neurogenesis and Myogenesismentioning
confidence: 99%
“…To determine whether pressure-induced decreases in Na/K-ATPase expression are accompanied by changes in cation homeostasis, we quantified inward flux of cations in purified, primary RGCs, using real-time thallium flux imaging (Weaver et al, 2004; Fischer et al, 2018). Thallium acts as a surrogate for cations and a fluorescent signal is generated by thallium binding to a cell-permeable Thallos dye (Weaver et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed ion channel activity in live RGC cultures exposed to 4 or 48 h of ambient or elevated pressure by thallium flux imaging, as previously described (Fischer et al, 2018). Thallium flux indirectly measures inward ion flux, through the fluorescence intensity of Thallos dye.…”
Section: Methodsmentioning
confidence: 99%
“…More broadly, coatings like polylysine are polycationic polymers, increasing cell attachment and outgrowth—but it is unclear whether there would be coupling between the coating and Gr/GO, masking direct biological effects. And recent studies have begun to systematically investigate the different biological effects observed even between different classes of ECM substrate (Fischer et al, 2018), suggesting that a single underlying mechanistic explanation of the biological effects of Gr must fully account for the composition of the substrate. The biological compatibility of Gr/GO substrates also does not appear to be cell-type specific, as retinal ganglion cells (Bendali et al, 2013; Fischer et al, 2018), cortical neurons (Rauti et al, 2016), hippocampal neurons (Veliev et al, 2016; Kitko et al, 2018; Pampaloni et al, 2018), and recently dorsal root ganglion neurons (Convertino et al, 2018) have all been cultured on bare Gr.…”
Section: Graphene and Neurons In Vitromentioning
confidence: 99%